2013
DOI: 10.1021/es4017848
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Related Alterations of Carbon Nanoparticles in Mammalian Cells Detected Using Biospectroscopy: Potential for Real-World Effects

Abstract: Nanotechnologies generate a wide range of engineered nanomaterials that enter into our ecosystem, especially carbon-based nanoparticles (CNPs). As these novel materials acquire ever increasing numbers of applications, they may pose a risk to organisms, including humans. However, our knowledge of nanoparticle-induced effects remains limited. We are yet to understand the interaction between nanoparticles and organisms, and classical toxicology fails to provide models for risk assessment. Biospectroscopy techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…45 This study has shown that CBNs induced a profile of alterations in vanbaalenii, carbohydrate was the potential marker. In both bacteria, the nanoparticles induced a similar ranking of alteration extent with C 60 causing the most significant differences.…”
Section: Discussionmentioning
confidence: 87%
“…45 This study has shown that CBNs induced a profile of alterations in vanbaalenii, carbohydrate was the potential marker. In both bacteria, the nanoparticles induced a similar ranking of alteration extent with C 60 causing the most significant differences.…”
Section: Discussionmentioning
confidence: 87%
“…The sensitivity of vibrational spectroscopy, especially ATR-FTIR spectroscopy, to identify low-level effects [104,105] that may lead to transformation (a precursor of malignancy) [106] has been demonstrated. Not only do computational algorithms allow one to classify according to cell type (or phenotype; also applicable to biofluids), but they also allow one to extract discriminating features that may give rise to a new concept of spectral biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information of the most widely used peak frequencies and their assignments refers to the reviews of IR spectroscopy 108 , Raman spectroscopy 52,87 , and ratios (X cm -1 /Y cm -1 ) 109 . These peaks with remarkable alterations are determined as discriminating biomarkers for diagnosis of changes resulted by specific exposures in many studies 69,87,104,105,108,110 . However, no biospectroscopy-relevant study has yet been found associated with biomarkers for antibiotic 13 resistance of microbiomes.…”
Section: Datasetmentioning
confidence: 99%